2020
DOI: 10.30544/514
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the optimal technology for copper leaching from old flotation tailings of the copper mine bor (Serbia)

Abstract: This work aimed to investigate optimal leaching technology for copper extraction from old flotation tailings of the Copper Mine Bor. The leaching degree of copper after leaching with sulphuric acid at 80 °C was 50%, the maximal leaching degree was achieved after 30 minutes. Then, old flotation tailings were leached with adapted moderately thermophilic acidophilic bacteria in a bioreactor at 40 °C. Maximal leaching degree of 84% was achieved after nine days of the experiment. The third leaching experiment was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…The reaction kinetics for leaching are very fast, as almost all of the leachable copper was in solution after 2 h (Figure 9), at least at an admittedly high acid concentration of 5% H 2 SO 4 . Similar kinetics were also described by [33]. The recovery of approximately 80% for the 2 M t of tailings with an average copper grade of 0.56% (Tables 9 and 10 refer to the coarse-grained material only) leads to around 8900 t of recoverable copper with a metal value of 49.1 M USD.…”
Section: Capacitysupporting
confidence: 74%
“…The reaction kinetics for leaching are very fast, as almost all of the leachable copper was in solution after 2 h (Figure 9), at least at an admittedly high acid concentration of 5% H 2 SO 4 . Similar kinetics were also described by [33]. The recovery of approximately 80% for the 2 M t of tailings with an average copper grade of 0.56% (Tables 9 and 10 refer to the coarse-grained material only) leads to around 8900 t of recoverable copper with a metal value of 49.1 M USD.…”
Section: Capacitysupporting
confidence: 74%
“…A multivariate function of seven independent variables and one dependent variable is defined from an inverse exponential model, a statistical analysis, and the multiple regression adjustment is presented in Eq. (11). R(X) = f(X) (11) Formalizing the optimization model, the objective is to maximize copper recovery considering the range of sampled values as domain of the input variables [67] expressed in Eq.…”
Section: Optimization Of the Experimental Modelmentioning
confidence: 99%
“…Pyrometallurgical processes generate large environmental liabilities, such as tailings dams [6][7][8] produced by flotation processes, which can affect acid rains and increase local pollution [9,10]. Hydrometallurgical processes, together with copper bioleaching processes [11][12][13], have proven to be more environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%
“…Reprocessing of tailings can enable reduction of the acid generation and following release of metals to waterways and soils by removing pyrite with simultaneous recovery of valuables. Several studies have been conducted at laboratory scale to recover copper and gold from the Bor tailings by acid leaching [8,15], acid leaching followed by flotation of leaching residue [16] leading to copper and sulfur recoveries of 70% and 77%, correspondingly. Conić et al [15] concluded, that the most efficient technology for copper recovery from the old flotation tailings of the Bor copper mine was leaching with biogenic lixiviant.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted at laboratory scale to recover copper and gold from the Bor tailings by acid leaching [8,15], acid leaching followed by flotation of leaching residue [16] leading to copper and sulfur recoveries of 70% and 77%, correspondingly. Conić et al [15] concluded, that the most efficient technology for copper recovery from the old flotation tailings of the Bor copper mine was leaching with biogenic lixiviant. Falagán et al [2] reached copper recoveries of over 90% by bioleaching.…”
Section: Introductionmentioning
confidence: 99%